2021
DOI: 10.1186/s40478-021-01219-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathological tau drives ectopic nuclear speckle scaffold protein SRRM2 accumulation in neuron cytoplasm in Alzheimer’s disease

Abstract: Several conserved nuclear RNA binding proteins (sut-1, sut-2, and parn-2) control tau aggregation and toxicity in C. elegans, mice, and human cells. MSUT2 protein normally resides in nuclear speckles, membraneless organelles composed of phase-separated RNAs and RNA-binding proteins that mediate critical steps in mRNA processing including mRNA splicing. We used human pathological tissue and transgenic mice to identify Alzheimer’s disease-specific cellular changes related to nuclear speckles. We observed that nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…Thus, polyserine alone is sufficient to mediate associations with tau aggregate in a length dependent manner. This provides a molecular explanation for the recruitment of the polyserine containing SRRM2 protein to tau aggregates in cell line and mouse models, as well as in patient samples (Lester et al, 2021;McMillan et al, 2021). Interestingly we also observed that 42, 20, 10, and 5-serine-Halo produced cytoplasmic foci that were not present in Halo alone (Figure 3A), suggesting polyserine has self-assembly properties (see below).…”
Section: Serine-rich Protein Domains or Polyserine Alone Are Sufficie...supporting
confidence: 56%
See 3 more Smart Citations
“…Thus, polyserine alone is sufficient to mediate associations with tau aggregate in a length dependent manner. This provides a molecular explanation for the recruitment of the polyserine containing SRRM2 protein to tau aggregates in cell line and mouse models, as well as in patient samples (Lester et al, 2021;McMillan et al, 2021). Interestingly we also observed that 42, 20, 10, and 5-serine-Halo produced cytoplasmic foci that were not present in Halo alone (Figure 3A), suggesting polyserine has self-assembly properties (see below).…”
Section: Serine-rich Protein Domains or Polyserine Alone Are Sufficie...supporting
confidence: 56%
“…Thus, polyserine alone is sufficient to mediate associations with tau aggregate in a length dependent manner. This provides a molecular explanation for the recruitment of the polyserine containing SRRM2 protein to tau aggregates in cell line and mouse models, as well as in patient samples (Lester et al, 2021; McMillan et al, 2021).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…We found that reducing the expression of BANF1 or ANKLE2 caused mislocalization of nuclear speckle component SRRM2 even without tau aggregation. Thus, the loss of nuclear envelope components alone initiated an event associated with tau pathogenesis in Alzheimer's disease (McMillan et al, 2021). Similarly, the disruption of Banf1, Ankle2, or Ppp2ca in mouse cortical neurons increased P-tau-Ser356 in the perinuclear and nuclear domains.…”
Section: Discussionmentioning
confidence: 97%